Salivary Cortisol Rhythms in Children With Cleft Lip and/or Palate: A Case–Control Study. (September 2018) - Sundell, Anna Lena; Marcusson, Agneta; Törnhage, Carl-Johan
Objective: Knowledge about the stress response in children with cleft lip and/or palate (CL/P) is sparse and the association between the stress response and health-related quality of life (HRQoL) is unknown. Consequently, investigations on the influence of CL/P on the stress response alone and its association with HRQoL are of importance. The purpose was to determine whether salivary cortisol concentration in children with CL/P differs from that in children without clefts (controls) and whether there are any differences in salivary cortisol concentrations between ages, gender, and type of cleft. Furthermore, the final aim was to determine the correlation between salivary cortisol concentration and HRQoL. Design: The study used a cross-sectional case-control design. Participants: Ninety-one 5- and 10-year-old children with CL/P and 180 age-matched controls. Main Outcome Measures: Salivary samples were collected on 2 mornings and 1 evening for each child. Samples were analyzed using a commercial competitive radioimmunoassay and HRQoL was assessed using the KIDSCREEN-52. Results: Salivary cortisol concentrations were similar in children with CL/P and controls. There was no difference in salivary cortisol concentrations between children with different types of cleft. There was no correlation between cortisol concentration and HRQoL. Conclusion: Five- and 10-year-old children with corrected CL/P seemed not to be more stressed than controls, and there were no correlation to HRQoL. The HRQoL levels - were comparable to that of a European norm population.